Parental behavior and anxiety in isogenic and outbred mice given access to two types of nesting materials - Moreira, Virgínia B. [UNESP] (2019)
The objective was to investigate if providing two types of nesting materials could modulate parental behavior and anxiety in laboratory mice. For that, 54 full-sib BALB/cJ and 50 randomly mated Swiss Webster mouse pairs were employed in a completely randomized designwith a 2 × 2 factorial arrangement (two genetic groups and with/ without access to nesting materials). Eight pieces of disposable polypropylene caps/ hairnets and 3 g of cotton were provided as nesting materials to half the cages from each genetic group. Maternal and paternal behaviors were recorded on the third reproductive cycle, twice a week, for three weeks, using scan sampling. The behaviors were recorded every 10 s for a period of 10 min (totaling 60 records)each day. Dams (N = 40)were tested in the elevated plus maze (EPM)on the fifth reproductive cycle, 7–10 days postpartum. Their 21-days-old weanlings (N = 208)were tested in the same apparatus. Total number of closed arm entries was used as measurement of motor activity, the percentage of time spent on open arms as measurement of anxiety and head dipping time as measurement of exploratory behavior. The provision of nesting materials increased the frequency of dams licking pups (1.72 ± 0.20 vs. 1.10 ± 0.21, P = 0.0342)and of sires resting in contact with pups (25.0 ± 1.5 vs. 18.9 ± 1.5, P = 0.0050), while simultaneously decreased the frequency of sires in non-contact rest with pups (6.4 ± 1.1 vs. 10.8 ± 1.2, P = 0.0074). Swiss Webster dams were recorded nursing their pups in the arched-back posture more frequently than BALB/cJ dams (9.63 ± 0.89 vs. 7.13 ± 0.86, P = 0.0187)and Swiss Webster sires showed a higher frequency of nest building than BALB/cJ sires (0.80 ± 0.16 vs. 0.31 ± 0.15, P = 0.0281). Motor activity was higher (8.00 ± 0.43 vs. 2.83 ± 0.41, P < 0.0001)and anxiety was lower (3.2 ± 28.4 vs. 2.4 ± 3.1%, P < 0.0001)in Swiss Webster than in BALB/cJ dams. Anxiety (26.6 ± 3.2 vs. 37.9 ± 3.5%, P = 0.0168)was also lower in Swiss Webster than in BALB/cJ weanlings. The availability of nesting materials increased the time dams spent in head dipping (10.9 ± 2.0 vs. 4.6 ± 1.9, P = 0.0087), but weanling behaviors in the EPM were unaffected. Slight differences in parental behavior and contrasting patterns of anxiety and motor activity were found between genetic groups. The provision of nesting materials promoted an intensification of favorable parent-offspring interactions and enhanced exploratory behavior of dams.